Tillage and Corn Residue Harvesting Impact Surface and Subsurface Carbon Sequestration. Issue 3 (1st May 2015) - Clay, David E.; Reicks, Graig; Carlson, C. Gregg; Moriles‐Miller, Janet; Stone, James J.; Clay, Sharon A.
Abstract : Corn stover harvesting is a common practice in the western U.S. Corn Belt. This 5‐yr study used isotopic source tracking to quantify the influence of two tillage systems, two corn ( Zea mays L.) surface residue removal rates, and two yield zones on soil organic C (SOC) gains and losses at three soil depths. Soil samples collected in 2008 and 2012 were used to determine 13 C enrichment during SOC mineralization, the amount of initial SOC mineralized (SOClost ), and plant C retained in the soil (PCRincorp ) and sequestered C (PCRincorp − SOClost ). The 30% residue soil cover after planting was achieved by the no‐till and residue returned treatments and was not achieved by the chisel plow, residue removed treatment. In the 0‐ to 15‐cm soil depth, the high yield zone had lower SOCloss (1.49 Mg ha −1 ) than the moderate yield zone (2.18 Mg ha −1 ), whereas in the 15‐ to 30‐cm soil depth, SOCloss was higher in the 60% (1.38 Mg ha −1 ) than the 0% (0.82 Mg ha −1 ) residue removal treatment. When the 0‐ to 15‐ and 15‐ to 30‐cm soil depths were combined, (i) 0.91 and 3.62 Mg SOC ha −1 were sequestered in the 60 and 0% residue removal treatments; (ii) 2.51 and 0.36 Mg SOC ha −1 were sequestered in the no‐till and chisel plow treatments, and (iii) 1.16 and 1.65 Mg SOC ha −1 were sequestered in the moderate and high yield zone treatments, respectively. The surface treatments influenced C cycling in the 0‐ to 15‐ and 15‐ to 30‐cm depths but did not influence SOC turnover in the 30‐ to 60‐cm depth.